Student’s Knowledge and Practices on Basic School Health Services in Relation to School Health Nurse Program - Poudyal, Jiwan Kumar; Sharma, Trishna; Parajuli, Sumitra; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2023)
IntroductionBasic school health services (BSHS) provided by the school nurse have the potential to significantly reduce the prevalent preventable health issues at school community. The objective of this study was to assess the of students on basic school health services in relation to school health nurse program. To assess the Students Knowledge and Practices on basic school health services in relation to school health nurse programMethodsAn analytical cross-sectional study conducted among 313 students on basic school health services in schools with and without implementation of school health nurse program using a non-probability purposive sampling technique. Data were collected using a self-administered questionnaire and an observation check list, and analyzed using descriptive and inferential statistics.ResultsThere is statistically significant difference in mean score of knowledge among students with School Health Nurse Program (SHNP) and not having school health nurse program. The practice of basic school health was significant association on how at comfort students felt when dealing with health issues (p